O amor e a dor na psicose: um estudo psicanalítico. - Cirilo, Éder Galiza (2020)
In psychoanalysis, love and pain are important affects for the formation of a subject, so that the singular manner they happen will reverberate in the psychic structuring. Love was defined by Freud as a libido investment, while pain was designated as an overload of inner excitement that could have been originated due to the cut of a libidinal bond. The psychic formation is branded by cuts of the libidinal bond to an object of love, having pain as the reaction, that thus must be assimilated and integrated so that the psyche maturation may occur. When the reaction to the pain turns to a very high level of inner libido overload, the subject may resort to a defense mechanism typical of psychosis, like the foreclosure. Starting from the principle that the pain must be worked so that the psyche maturation can occur, and taking as foundation Juan-David Nasio’s proposition that the pain consists in the last affect before psychoses befalls, this work questions if psychosis would derive from a state of nontolerance to pain, connected to displeasure, due to excessive love directed to the inside of psyche. On these terms, we sustain the proposition that psychosis derives from a failure of the psyche in working big libidinal excitements invested in inner representations. We take for basis Jacques Lacan’s proposition about the notion of clinical structure, in which psychosis derives from a failure in the Law of the Father, a concept referring to a cut that interrupts the bond with the object of love, what allowed us to catch a glimpse of a possible link between the intervention of the Law of the Father and the pain. The goal of this study was to analyze the place of love and pain in the formation of psychosis. For this reason, we have made an bibliographical research in psychoanalysis referring to the topic of love, pain and psychosis in Freud’s psychological works and in some of the seminars of Jacques Lacan, and all that in dialogue with contemporary authors, aiming to enclose in the first one the concepts of love, pain and psychosis and, in the latter, to understand how the formation of an subject happens, and specially the formation of psychosis.At the end of this study, we point out the love in psychosis as a predominance of passive love. This one is a pain intolerance reaction connected to the displeasure that appears from the cut made by castration, time of psychic organization that allows the formation of the subject starting from the change in the predominance from the place of being loved to the place of loving. Love, in psychosis, seeks to fasten itself to a passive place, renouncing the possibility of becoming a subject of desire in order to become the object of the Other’s satisfaction. About that place, we also highlight that pain in psychosis is different from the pain that occurs in neurosis. Pain ins psychosis is beyond the limit of an inner displeasure, occurring in a field which is enjoyment itself. The results of this study have brought metapsychological inputs to the clinics of psychosis, amplifying the clinical view by emphasizing the subtleties of love and pain in the formation of psychosis.